2021
DOI: 10.1016/j.rinp.2021.104845
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models for COVID-19 cases, deaths and recoveries in Algeria

Abstract: This study was conducted to predict the number of COVID-19 cases, deaths and recoveries using reported data by the Algerian Ministry of health from February 25, 2020 to January 10, 2021. Four models were compared including Gompertz model, logistic model, Bertalanffy model and inverse artificial neural network (ANNi). Results showed that all the models showed a good fit between the predicted and the real data (R 2 >0.97). In this study, we demonstrate that obtaining a good fit of real dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These operations are performed using matrix multiplication and pointwise operations followed by nonlinear activation functions. This carefully orchestrated mechanism allows LSTMs to model complex sequences, making them suitable for various applications [ 58 , 93 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These operations are performed using matrix multiplication and pointwise operations followed by nonlinear activation functions. This carefully orchestrated mechanism allows LSTMs to model complex sequences, making them suitable for various applications [ 58 , 93 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tamang et al. (2020) used an ANN to construct a forecasting model for confirmed and fatal COVID-19 cases in India, the USA, the UK, and France, whereas Lounis et al. (2021) developed an inverse ANN model to estimate COVID-19 cases, deaths, and recoveries in Algeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Motallebi et al (2022) [13] examined the association between face-covering mandates and the COVID-19 mortality decline accross 44 countries in 2 continents, and found that the COVID-19 death rate is lower in countries with face-mask mandates than in countries without mandates. Lounis et al (2021) [12] made a comparison of four models: Gompertz, Logistic, Bertalanffy and inverse artificial neural network (ANNi), with the aim of predicting the number of COVID-19 cases, deaths and recoveries in Algeria. For predicting death cases, they showed that the Gompertz model obtained the best precision with a minimum error of 1.14%.…”
Section: Introductionmentioning
confidence: 99%